Analysis of Comparative Figures of Speech in the Anthology of Poetry Ruang Kata by Luckyansyah, et al 2020 - Nafila Nafila; Sapiin Sapiin; Murahim Murahim (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Comparative figures of speech such as metaphors, similes, and personifications serve to provide depth and richness of meaning in poetry in the poetry anthology Ruang Kata by Bastrindo E 2020. This figure of speech is used to connect experiences, emotions, or observations with other objects, thus enriching the meaning of the poem. For example, in the poetry anthology Ruang Kata by Luckyansyah, et al., 2020, it describes feelings of loss using strong comparisons, readers can feel the depth of these emotions. Thus, comparative figures of speech play an important role in strengthening the theme and providing a richer aesthetic experience to readers. This type of research is qualitative descriptive because it focuses on procedures or strategies and approaches to solving research problems that involve the exposure and description of the situation of the research object. This research is included in the type of qualitative descriptive research because it focuses on the process of describing words or sentences containing comparative figures of speech in the Ruang Kata Poetry Anthology by Luckyansyah, et al., 2020. Based on the formulation of the problem in this study. Will describe the types of comparative figures of speech in the poetry anthology Ruang Kata by Luckyansyah, dkk 2020. The data found by researchers from 11 types of comparative figures of speech obtained only 5 types of comparative figures of speech in the Ruang Kata Poetry Anthology by Luckyansyah, dkk 2020. including, personification figures of speech totaling 13 data, metaphor figures of speech totaling 29 data, simile figures of speech totaling 13 data, symbolic figures of speech 5 data, and hyperbole figures of speech 9 data. Based on the formulation of the problem in this study, the comparative figures of speech in the Ruang Kata poetry anthology by Luckyansyah, et al., 2020 were studied. The researchers found 5 types of comparative figures of speech in the anthology, namely personification, metaphor, simile, symbolic, and hyperbole.